Fabrication and characterization of hybrid microwave assisted sintering Sn-0.7Cu + 1.0wt.% Si₃N₄ composite solder - Flora, Somidin (Universiti Malaysia Perlis (UniMAP), 2019)
One of the leading choices in upgrading the properties of existing lead-free solder alloys is by composite technology approach, whereby high technical ceramic particles can be added into the solder alloy matrix. Accordingly, Sn-0.7Cu + 1.0wt.% Si₃N₄ composite solder was synthesized using powder metallurgy routes which consist of blending, compaction and sintering. This research introduced a hybrid microwave assisted sintering process which can sinter ceramic-reinforced composite solder at approximately 185˚C within 2 minutes without holding time and protective inert gas. In order to evaluate the compatibility of hybrid microwave assisted sintering approach in ceramic-reinforced composite solder development, a detailed comparison of the process and properties of conventionally sintered and microwave sintered samples of Sn-0.7Cu + 1.0wt.% Si₃N₄ composite solder was performed. Identical sintering temperature at 185 ˚C was used for both types of sintering, in which conventional sintering was performed using a tube furnace in an argon atmosphere for 2 hours. The monolithic Sn-0.7Cu solder sample was also synthesized as control sample in a similar way. Hybrid microwave assisted sintering method showed significant advantages in processing compared to conventional sintering method, such as rapid heating rate, shortened sintering time, less energy consumption and much less expensive equipment. The influence of different sintering methodologies on Sn-0.7Cu + 1.0wt.% Si₃N₄ bulk solder sample were investigated based on the density, porosity, microhardness, microstructures, wettability and intermetallic compound thickness on Cu-substrate. It was noted that microwave sintering method can densify the Sn-0.7Cu + 1.0wt.% Si₃N₄ composite bulk solder green compact in a short time, however, conventional sintered sample showed better density and porosity. Interestingly, finer and well-distributed precipitates were observed in microwave sintered samples. This has led to higher microhardness performance observed in microwave sintered sample (12.0 ± 0.2 HV) compared to the conventionally sintered sample (11.2 ± 0.1 HV). The wettability performance of Sn-0.7Cu + 1.0wt.% Si₃N₄ composite solder on Cu-substrate was slightly reduced with microwave sintering approach, however, insignificant difference of intermetallic compound thickness was observed in both microwave sintered and conventionally sintered samples. Overall, hybrid microwave assisted sintering showed better processing with promising properties on ceramic-reinforced Sn-0.7Cu + 1.0wt.% Si₃N₄ composite solder.